Elite industrial associada: uma análise a partir das políticas públicas de incentivos fiscais em Goiás - Laurias, Nathalia Cordeiro (2016)
The object of this thesis is related to the associated industrial elite, concept which was developed with the order to identify the peculiarities of this elite, and having the goiana industrial reality as a space for the verification of its applicability, from the public politics of tax incentives, especially the Programa de Desenvolvimento Industrial de Goiás (PRODUZIR). We also opted, to restrict the influence of this elite only to aspects related the world of work. Our empiric universe turns to two important industry associations in Goiás, which are, the Federação das Indústrias do Estado de Goiás (FIEG) and the Associação Brasileira Pró- Desenvolvimento Industrial (ADIAL). The research offers quantitative analyses, as well, occupy place of major the analysis of speech, in attempt to give methodological complement to the thematic study. Throughout this research we identified how the associated industrial elite negotiates its demands directly to the State, and takes advantages of the public machine in defense of its interests, as well, uses the media to fix in the individuals' imaginary about the importance of these public policies. At the end of this research we confirm the thesis of the existence of the associated industrial elite in Goiás from the set of tools to your interests.